The Influence Of Audit Fee And Competency On Audit Quality Moderated By Professionalism At Kaps In Indonesia - Rani Chrisna Putri; Rida Perwita Sari; Rizdina Azmiyanti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to examine and analyze the influence of audit fee and competency on audit quality which is moderated by professionalism at KAP in Indonesia. The type of research applied in this research is a quantitative approach. The selected population was all auditors who worked at KAPs in Indonesia and were registered in the 2023 IAPI Directory. The sample was selected using convenience sampling techniques and obtained 97 respondents. This research uses WarpPLS 8.0 software as a data analysis tool. The research results show that audit fee and competency can influence audit quality at Indonesian KAP. Professionalism can also strengthen the influence of audit fee on audit quality, but cannot moderate the influence of competency on audit quality at KAPs in Indonesia.